Possible significance of degeneration and decreased expression of progesterone receptor in postmenopausal uterine leiomyoma - Saki Tanioka; Ryoko Asano; Reina Wakabayashi; Hiroyuki Hayashi; Hiroyuki Shigeta (BMC, 2022)
Abstract Background The growth of uterine leiomyomas is dependent on the levels of sex steroid hormones, and they usually shrink after menopause. However, there are cases in which leiomyomas continue to grow and/or surgery is required after menopause. In addition to estrogen, progesterone has recently been implicated in leiomyoma enlargement, but its relevance to postmenopausal leiomyoma remains unknown. Therefore, we investigated whether hormone receptor expression is associated with postmenopausal leiomyoma enlargement and characterized pathological findings of postmenopausal leiomyoma, which have not been clarified yet. Methods Nine cases that required total hysterectomy for leiomyomas after menopause were examined. Surgeries were conducted because of pelvic pressure, pelvic pain, suspected malignancy, or growing leiomyoma. Six cases of leiomyomas being incidentally found during total hysterectomy for postmenopausal uterine prolapse, and six patients who underwent hysterectomy for leiomyomas before menopause, were examined as controls. We evaluated the expression of estrogen receptor, progesterone receptor B, and progesterone receptor AB by immunohistochemical staining among the cases. We also analyzed the pathological findings of leiomyomas. Results In postmenopausal leiomyomas, the expression of progesterone receptor was higher than that in the adjacent myometrium. Compared with premenopausal leiomyomas, the expression of progesterone receptor decreased. Postmenopausal leiomyomas that required surgery did not show elevated sex steroid hormone receptor expression, compared with the leiomyomas that did not require surgery. The degeneration frequency of leiomyomas was 92% in the group that underwent surgery for postmenopausal leiomyomas, 65% in the group that underwent surgery for reasons other than the presence of leiomyomas after menopause, and 47% in the group operated for leiomyomas before menopause. Conclusions These results suggest that sex steroid hormones are unlikely to be associated with the growth of leiomyomas after menopause. Since leiomyoma degeneration with increased extracellular matrix is likely to occur in postmenopausal women, the degeneration of leiomyomas may be the main mechanism for the growth of postmenopausal leiomyomas.